Review: Safe and sustainable groundwater supply in China - Wang, Yanxin; Zheng, Chunmiao; Ma, Rui (Hydrogeology journal, 2018)
Exploitation of groundwater has greatly increased since the 1970s to meet the increased water demand due to fast economic development in China. Correspondingly, the regional groundwater level has declined substantially in many areas of China. Water sources are scarce in northern and northwestern China, and the anthropogenic pollution of groundwater has worsened the situation. Groundwater containing high concentrations of geogenic arsenic, fluoride, iodine, and salinity is widely distributed across China, which has negatively affected safe supply of water for drinking and other purposes. In addition to anthropogenic contamination, the interactions between surface water and groundwater, including seawater intrusion, have caused deterioration of groundwater quality. The ecosystem and geo-environment have been severely affected by the depletion of groundwater resources. Land subsidence due to excessive groundwater withdrawal has been observed in more than 50 cities in China, with a maximum accumulated subsidence of 2–3 m. Groundwater-dependent ecosystems are being degraded due to changes in the water table or poor groundwater quality. This paper reviews these changes in China, which have occurred under the impact of rapid economic development. The effects of economic growth on groundwater systems should be monitored, understood and predicted to better protect and manage groundwater resources for the future.